Autoimmune Congenital Heart Block: A Review of Biomarkers and Management of Pregnancy - De Carolis, Sara; Garufi, Cristina; Garufi, Ester; De Carolis, Maria Pia; Botta, Angela; Tabacco, Sara; Salvi, Silvia (Frontiers in Pediatrics, 2020)
Autoimmune Congenital Heart Block (CHB) is an immune-mediated disease due to transplacental passage of circulating anti-Ro/SSA and anti-La/SSB autoantibodies. It occurs in 2% of anti-Ro/SSA-exposed pregnancies, and recurrence rate is 9 times higher in subsequent pregnancies. Aim of this review is to identify biomarkers of CHB and treatment strategies. The Ro-system is constituted by two polypeptides targeted by the anti-Ro52 and anti-Ro60 autoantibodies. The central portion of Ro52 (p200), more than the full amino-acid sequence of Ro-52, is recognized to be the fine specificity of anti-Ro associated to the highest risk of cardiac damage. If anti-p200 antibody should be tested, as biomarker of CHB, over standard commercial ELISAs is still debated. Recent studies indicate that type I-Interferon (IFN) can activate fibroblasts in fetal heart. In the mother the anti-Ro/La antibodies activate the type I IFN-signature, and maternal IFN-regulated genes correlate with a similar neonatal IFN-gene expression. Evaluation of maternal IFN-signature could be used as novel biomarker of CHB. The measurement of “mechanical” PR interval with weekly fetal echocardiogram (ECHO) from 16 to at least 24 weeks of gestation is strongly recommended for CHB prenatal diagnosis. However, ECHO screening presents some limitations due to difficult identification of first-degree block and possible occurrence of a complete block from a normal rhythm in few days. Maternal administration of Hydroxychloroquine from the 10th week of gestation, modulating toll-like receptor and autoantibody-dependent type I IFN activation on the fetus, has an important role in preventing CHB in pregnant women with high risk for recurrent CHB.